Microcostatus salinus sp. nov., a new benthic diatom (Bacillariophyceae) from esturarine intertidal sediments, Japan - Li, Yuhang; Suzuki, Hidekazu; Nagumo, Tamotsu; Tanaka, Jiro; Sun, Zhongmin; Xu, Kuidong (Phytotaxa, 2016)
Microcostatus salinus, an epipsammic species, is described from estuarine intertidal sediments in Japan. Its morphology was examined with light, scanning and transmission electron microscopy. Microcostatus salinus possesses two unique morphological features differing from all other species in this genus, viz., i) the striae are composed of two elongate areolae and restricted to the area near valve apexes, and ii) the distance between the two central raphe endings on the external valve surface is about two times longer than that on the internal one. In addition, M. salinus is the only species of the genus Microcostatus found from brackish to saline environments.